Morphological state of the renal medulla in rats in case of an experimental burn injury under conditions of gekoton. - O. I. Kovalchuk; V. G. Cherkasov; V. A. Pastukhova; O. V. Malikov (Морфологія, 2018)
Background. The article presents structural changes of the renal medulla in experimental traumatic skin injury in rats under conditions of intravenous infusion of a colloid-hyperosmolar solution of gekoton. It was found that gekoton acts on the structure of the body as a cytoprotector. Objective. To study structural changes of the renal medulla in case of an experimental skin burn injury in rats under conditions of an intravenous infusion of gekoton. Methods. Macroscopic, histological, electron microscopic, laboratory, statistical analysis. The experimental study of morphological changes of the renal medulla in case of burn disease (within 1, 3, 7, 14, 21, 30 days) under condition of exposure to 0,9 % NaCl solution and an infusion of colloidal hyperosmolar drugs with detoxicating, rheological, energetic, antishock effect gekoton and lactoproteinum with sorbitol has been executed in 90 male Wistar rats of 155-160 g. Results. The destruction of microvilli of limbus penicillatus and the breakage of apical region epithelial cells cytoplasm of proximal convoluted tubules of the nephron are typical for the renal medulla in rats with skin burns which were given the gekoton solution during the first three days, one and three days after the experiment began. Conclusion. In case of an experimental skin burn of ІІ-ІІІ grade of 21-23 % of body surface area in rats a remarkable cytoprotective effect of gekoton on the structure of the renal medulla is a morphologic equivalent of positive effect of an intravenous infusion of gekoton. The above-mentioned cytoprotective effect is caused by the induction of mitochondria hypertrophy and hyperplasia, as well as the stimulation of mitophagy which provides the removal of damaged mitochondria and suppresses the progress of cell apoptosis.